Increased Activity of Hippocampal Antioxidant Enzymes as an Important Adaptive Phenomenon of the Antioxidant Defense System in Chronically Stressed Rats - Popović, Nataša; Pajović, B. Snežana; Stojiljković, Vesna; Todorović, Ana; Pejić, Snežana; Pavlović, Ivan; Gavrilović, Ljubica (Acta veterinaria (Beograd), 2017)
This study examined the effects of chronic restraint stress (CRS: 2 hours × 14 days) on gene expression of three antioxidant enzymes, copper, zinc superoxide dismutase (SOD 1), manganese superoxide dismutase (SOD 2) and catalase (CAT) in the rat hippocampus. Also, we examined changes in the activities of SOD 1, SOD 2 and CAT in the hippocampus of chronically stressed rats. Investigated parameters were quantifi ed by using real-time RT-PCR, Western blot analysis and assay of enzymatic activity. We found that CRS did not change mRNA and protein levels of SOD 1 and CAT, but increased mRNA and protein levels of SOD 2. However, CRS treatment increased the enzyme activities of SOD 1, SOD 2 and CAT. Our fi ndings indicate that the increased activity of antioxidant enzymes (SOD 1, SOD 2 and CAT) in the hippocampus may be an important adaptive phenomenon of the antioxidant defense system in chronically stressed rats.